Refugees and social capital: Evidence from Northern Lebanon - Anselm Hager; Justin Valasek (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2020)
Despite numerous studies on the social and political impact of refugees in Europe, we have very little systematic evidence on the impact of refugee settlement on social cohesion in the developing world. Using data gathered in Northern Lebanon, we show that increased salience of the "refugee crisis" decreases natives' trust and prosocial preferences toward refugees, suggesting a negative impact of mass refugee settlement. However, this negative impact is driven exclusively by respondents with no individual exposure to refugees. In fact, despite concerns that refugee settlements may result in local conflict, we find that individual proximity to refugees is positively correlated with trust towards refugees, and that proximity has a positive spillover effect on social capital towards other migrants. This implies that, while the refugee crisis may have had a negative impact on social cohesion, this negative impact is mitigated in areas where natives are in contact with refugees.
Keywords: F22; H41; D74; 330; migration; social capital; experiment; ethnicity